Pencegahan Praktik Pembulian di Sekolah dengan Ayat Al-Qur'an dan Hadist - Fadhila Fadhila; Fajriatun Nurjanah; Ikrimatul Adawiyah Siregar; Wildan As'at Taufik Hasibuan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study confirms that bullying is a serious problem in educational environments that negatively impacts students' psychological, social, and academic aspects. Based on the values of the Qur'an and hadith, the study emphasizes the important role of Islamic teachings as a moral foundation in preventing bullying, especially through communication ethics, such as qaulan sadida (speaking honestly, politely, and without causing harm). The prevention strategies developed include strengthening character education based on Islamic values, integrating school policies based on Islamic values, and implementing innovative educational media. This approach is also balanced with policy and legal synergy, including Islamic law and the Electronic Information and Transactions Law (ITE Law) in the context of cyberbullying. Through the Digital Research Methods, religious discourse on YouTube and TikTok social media was analyzed to understand public perceptions of bullying and Islamic values. The results showed that the comprehensive integration of verses from the Qur'an and hadiths could be a systematic, holistic, and relevant model for preventing bullying in the digital age.